The Relationship between Healthcare Expenditure and Economic Growth In the Gulf Cooperation Council Countries (GCC): An Applied study using Co-integration Test and Causality - Ageli, Mohammed (The Arab Journal of Administration, 2021)
King Saud University, Riyadh، Saudi Arabia The Gulf Cooperation Council (GCC) is giving more importance to human resource development in which healthcare and education are two prime components. In this study, we examine the casualty effect between healthcare spending GDP in GCC countries during the period 2000-2020 using panel cointegration approach using cointegration and causality between health expenditure and economic growth. We found that there is a long cointegrated between the two variables for individual country. This study also reports that health expenditure and economic growth are cointegrated in all the GCC countries telling the presence of long run association between them. The Granger panel causality test confirms the presence of bidirectional causality between the variables, indicating feedback effect between these two variables, both in the short run and long run. The results shows that there is bi- directional (Saudi Arabia and UAE), unidirectional (Bahrain) and no causality (Oman) between health spending and economic growth. In conclusion, this study suggests that health expenditure should be regarded as a critical factor to help sustain human resource development (to create healthy and productive labour market) that helps in economic growth in Saudi Arabia.